Legal Regulation of Passenger Transportation by Rail in the Republic of Uzbekistan (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Railway transport occupies a special place in the economic development of the Republic of Uzbekistan. One of the priorities of state policy is the transportation of passengers in the country, ensuring their safety, improving the quality of service and creating a transport system that meets environmental requirements. The effective operation of railway transport determines not only economic stability, but also social development, connectivity between regions and population mobility. Therefore, the correct formation of legal and regulatory frameworks in the field of passenger transportation is one of the urgent issues. This article fully covers the legal framework for rail transport.